2011
DOI: 10.1111/j.1749-4877.2011.00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary seed dispersal by dung beetles in an Amazonian forest fragment of Colombia: influence of dung type and edge effect

Abstract: Seeds of many plant species are secondarily dispersed by dung beetles, but the outcome of this interaction is highly context-specific. Little is known about how certain anthropogenic disturbances affect this plant-animal interaction. The aims of this study were to assess the effect of dung type on secondary dispersal by dung beetles in a forest fragment, and to determine whether this interaction is affected by edge effects. Using pitfall traps, we captured dung beetles attracted to dung of 2 frugivorous mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…These results clearly demonstrate the relevance of empirically estimating the amount of ecological functions rather than deducing it from community attributes, as has already been pointed out by previous studies [26], [52]. Furthermore, among the functional variables, dung removal was the least sensitive to habitat disturbance.…”
Section: Discussionsupporting
confidence: 85%
“…These results clearly demonstrate the relevance of empirically estimating the amount of ecological functions rather than deducing it from community attributes, as has already been pointed out by previous studies [26], [52]. Furthermore, among the functional variables, dung removal was the least sensitive to habitat disturbance.…”
Section: Discussionsupporting
confidence: 85%
“…Losey & Vaughan, ; Nichols et al , ; Beynon et al , ); germination and/or secondary dispersal of seeds owing to dung relocation by beetles (e.g. D'hondt et al , ; Santos‐Heredia et al , ; Midgley et al , ); dung beetle behaviour associated with provisioning/relocation of food for the larvae (e.g. Halffter & Edmonds, ; Klemperer, ; Dacke, ; Dacke et al , ); dung preferences (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Fedriani and Manzaneda (2005) also found that seeds located in sheltered microsites experience higher removal by seed predators compared with seeds in open microsites. Therefore, spatial patterns of seed predation and plant-animal interactions are not only affected by rodent population densities, but also by other factors, such as habitat type (Calvĩno-Cancela & Martín-Herrero 2009), the degree of disturbance or habitat degradation (Cole 2009), seed availability and habitat physiognomy (Díaz 1992), predator's preferences (Vanhoenacker et al 2009), habitat preferences of predators (Manson & Stiles 1998) or edge effects (Notman et al 1996;Santos-Heredia et al 2011). Furthermore, the high seed predation number in the wild banana stands might reduce competition between seed -1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 lings and parent plants, according to the escape hypothesis of Janzen-Connell (Janzen 1970;Connell 1971).…”
Section: Discussionmentioning
confidence: 99%